Modeling Multivocality in a U.S.-Mexican Collaboration in Writing Across the Curriculum - Poe, Mya; Craig, Jennifer (Journal of Academic Writing, 2011)
Since 2006 the ‘Antwerp Group’ group has explored student writing from various country perspectives to understand what practices and pedagogies are country specific and what issues cut across national borders. The insights of the Antwerp Group helped inform a 2009–2010 collaboration between The Massachusetts Institute of Technology and the Instituto Tecnológico y de Estudios Superiores de Monterrey in which we combined Writing Across the Curriculum (WAC) and English as Foreign Language (EFL) instruction. This paper describes how a theoretical model used by the Antwerp Group helped us identify the multivocality that each collaborating group brought to this new partnership. In the end, theorizing multivocality helped us recognize our diverse perspectives as a resource even as we sought to find a collaborative voice in setting project goals, defining a student survey, and implementing a curricular design for a WAC-EFL writing course.